Effects of Burial Depth on the Seismic Response of Subway Station Structure Embedded in Saturated Soft Soil - Xuelei Cheng; Zongguang Sun (Advances in Civil Engineering)
For the aim to study the effects of burial depth on seismic response in the subway station’s structure embedded in saturated soft soil, on the basis of the OpenSEES program, numerical models with four cases of burial depth for the nonlinear interaction system including subway station’s structure and saturated soft soil are developed with the u-p formulations of Biot’s theory as it seeks to describe the saturated two-phase media. The effects of burial depth on the seismic response and the failure pattern of the subway station structure are investigated. The numerical results show that (1) the burial depth has a significant effect on the nonuniform uplift of station’s structure due to the movement of soil from far field towards baseplate; (2) with the increase of burial depth, the inertial effect of overlaying soil of the subway station structure becomes more obvious, and the peak zone of the pore pressure ratio contracts from the outer area to the baseplate bottom with decreasing amplitude; (3) the dynamic index R decreases with the increasing burial depth of the station’s structure; and (4) in terms of the middle column, the burial depth of the station’s structure has the most crucial effect on the additional dynamic shear force and bending moment at the top end.